Reformulation of the Return of State Losses as the Basis for Terminating Investigations into Corruption Crimes - Widia Dewi Anggraini; Hafrida; Erwin (Melayunesia Law, 2025)
This article discuss issue law about urgency of reform of Article 4 of the Law Eradication Action Criminal Corruption in relation with recovery loss state finances and effectiveness enforcement law. Focus study directed at the problems implementation Article 4 which in practice does not provide incentives for perpetrators to recover state financial losses, because even though the losses have been recovered, the legal process continues without any different consequences. The research method used is a normative juridical approach by examining relevant laws and regulations, court decisions, and law enforcement practices. The results of the analysis indicate that the criminal system that emphasizes the retributive aspect is not fully in line with the objectives of national law, namely realizing the benefits and recovery of state finances. As a solution, this study proposes a reformulation of Article 4 by setting a limit of the value of losses below IDR 1 billion, the investigation of which can be stopped if the perpetrator has returned the entire principal loss along with interest and consequences. This approach aims to streamline law enforcement, encourage perpetrators' awareness in recovering state losses, and emphasize the orientation of criminal law on corruption towards restorative fiscal justice. Thus, this reformulation is expected to be able to balance legal certainty, benefits, and justice in efforts to eradicate criminal acts of corruption in Indonesia paragraph.